Pengaruh Tenaga Kerja dan Investasi terhadap Pertumbuhan Ekonomi di Provinsi Jambi - Jannah, Raudhatul; Hasminidiarty, Hasminidiarty (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The aims of the study were to determine: (1) the effect of labor on economic growth in Jambi Province; (2) the effect of investment on economic growth in Jambi Province, and (3)tThe effect of labor and investment on economic growth in Jambi Province. The type of data used in this study is published secondary data, namely in the form of time series for 14 years in Jambi Province from 2010-2023. The source of the data obtained is from the Central Bureau of Statistics (BPS) Jambi Province. This study uses multiple linier regression analysis. Data analysis prerequisite test used normality test, multicollinearity test, autocorrelation test and heteroscedasticity test. The hypothesis test used is the coefficient of determination R square, the F test and the t test. The results of this study indicate that partially: (1) labor has a significant positive effect on economic growth in Jambi Province; (2) investment has a significant positive effect on economic growth in Jambi Province; and (3) simultaneously labor and investment have a significant effect on economic growth in Jambi Province.